Training Course Results of the Assessment of Modified Rodnan Skin Score in Scleroderma - Can, Gercek; Koken Avsar, Aydan; Kocaer, Sinem Burcu; Kenar, Gokce; Solmaz, Dilek; Onen, Fatos; Birlik, Merih (Galenos Publ House, 2022)
Aim: Modified Rodnan Skin Score (mRSS) is generally used to assess skin involvement in patients with scleroderma. There are conflicting data on the effectiveness of mRSS training courses in previous studies. The aim of this study to evaluate the effectiveness of a mRSS training course applied to rheumatology minor residents. Materials and Methods: Ten rheumatology minor residents were included in the study. The participants were given a 1 -hour theoretical training including skin involvement in scleroderma and mRSS evaluation, by three experienced rheumatology specialists. Then training continued with performing mRSS on 4 patients with scleroderma for 1 hour. Participants made scores on a paper form on 2 patients before and after the training, including 17 regions, and the total score was between 0 and 51. Inter- observer reliability for pre- and post -training was evaluated with intra-class correlation coefficient (ICC) analysis. Agreement was evaluated with Fleiss's kappa according to 12 different score regions before and after the training. Results: The ICC was detected as 0.867 [95% confidence interval (CI): 0.625-1.00, p=0.05] before the training, and 0.905 (95% CI: 0.045-1.00, p=0.02) after the training. When the regions of mRSS were evaluated individually, an increase in agreement was observed in some of the scores while there was no change in one region and a decrease in agreement was observed in some. Conclusion: This study has shown that mRSS is an effective scoring that can be easily conveyed with training courses.
Keywords: Scleroderma; skin thickening; modified Rodnan Skin Score; training